ANALISIS LUAS DAERAH TANGKAPAN AIR DAN DEBIT BANJIR RENCANA DI KM 63+100 SAMPAI 63+200 ANTARA STASIUN RANDUBLATUNG DAN STASIUN DOPLANG DAOP 4 SEMARANG PT KERETA API INDONESIA (PERSERO) - Dicky Arisikam; Heru Kuswanto; Muhammad Arifudin; Felicitas Cidandra Christy (Jurnal Ilmiah Teknologi Infomasi Terapan, 2022)
that plays an important role in the movement of people, not only in the movement of people but in distributing goods. The train is called the safest mode of transportation because it has its own track. However, there are several obstacles that obstruct train operations, which is natural disasters. In June 2022 there was a landslide on the Km. 63+100 up to Km. 63+200 between Doplang Station and Randublatung Station, Daop 4 Semarang. One of the causes of landslides is scouring at river bends. In the outer bend area of ??the river where the flow velocity is relatively high, erosion occurs which erodes the river body. Therefore, with the help of ArcGIS 10.5 software, the catchment area is 112.876 km2 (calculated), which is one of the parameters to calculate the amount of flood discharge. By using the Nakayasu method, the 25 years return period flood discharge at the problem area is 353.3 m3/s.